Implementasi Smartquail Incubator Pada Peternakan Burung Puyuh Cv. Suga Jaya Barokah, Banyumas - Hidayanto, Nur; Muis, Deny Rozaqul; Hastama, Firman Bayu (Universitas Muhammadiyah Sukabumi, 2022)
Wlahar Kulon Village, Patikraja District, Banyumas has a community of quail breeders (Coturnix coturnix japonica), one of which is Pak Herman. Partner problems are the microclimate of the cage which is uncomfortable, not yet equipped with precise tools and there is only one fan for the building. This condition causes low egg production and egg shell quality. The optimal environmental temperature for quail production period is 28-32°C. Temperatures that are too high cause the egg shells to be thin and easily cracked and make the quail stressed and die easily. The purpose of this PKM-PI is to increase the productivity of quail using the Smartquail Incubator tool and to apply and develop it in order to achieve economic independence for quail farmers. The method of implementing this program consists of conducting surveys and literature studies, designing and manufacturing tools, calibrating sensors, testing tools, evaluating tools, as well as mentoring and monitoring. The results after applying the Smartquail Incubator tool to quail farmers are that the cage temperature control becomes automatic, the energy needed to manage quail is only 2 hours/day, production increases to 38.2 kg/month, mortality decreases to 3 fish/month, quail egg shell becomes thicker, and uses a hybrid electric energy source, namely a combination of PLN and solar panels. Smartquail Incubator uses a microcontroller equipped with an LCD as a means of regulating and monitoring the temperature conditions of the cage. Smartquail Incubator can be controlled with a Smartphone remotely because it already uses the Internet of Things system. The conclusion obtained is that the Smartquail Incubator is an alternative for quail breeders to increase quail productivity. The development of the Smartquail Incubator helps farmers to achieve economic independence.